Enhancing the cycling stability of all-solid-state lithium-ion batteries assembled with Li1.3Al0.3Ti1.7(PO4)3 solid electrolytes prepared from precursor solutions with appropriate pH values. Issue 7 (May 2020) - Kou, Zhiyan; Miao, Chang; Mei, Ping; Zhang, Yan; Yan, Xuemin; Jiang, Yu; Xiao, Wei
Abstract: NASICON-type solid electrolyte powders Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP) are synthesized by spray-drying and assisted sintering processes. The effects of different pH values of the spray-dried precursor solution on the crystallinity, morphology, ionic conductivity, compaction density and cycling stability of the LATP solid electrolyte sheets are investigated. The LATP-6.0 solid electrolyte sheets present the most perfect microstructure with a compaction density of 2.968 g cm −1 and the highest ionic conductivity of 1.182 E−4 S cm −1 with an activation energy of 0.273 eV at room temperature when the pH value of the precursor solution is adjusted to 6.0. Additionally, the assembled LiCoO2 /LATP-6.0/Li all-solid-state coin cell delivers commendable cycling stability with a high discharge specific capacity of 150.5 mAh g −1 at 0.1 C after five activation cycles and retains a specific capacity retention rate of 94.28% after 300 cycles with various current densities at room temperature. Moreover, the LATP-6.0 solid electrolyte sheets maintain an intact morphology and uniformly-distributed elements composition after cycling. Based on these excellent results, the use of the LATP-6.0 sheets as solid electrolytes in high-performance all-solid-state lithium-ion batteries is a promising strategy.